The Development Of A National Integrated Data System For Malaysia: A Proposal For A Pilot Study - Salih, Kamal; Ratnam, K.J. (USM, 1975)
After two decades of development experience that can be regarded by most standards to be extremely successful, and now entering another five-year phase with the inception of the Third Malaysia Plan, planners, policy-makers and administrators have found themselves faced with an even greater array of problems of managing the economic and social progress of the country.